Framing impacts on citizen science data collection and participant outcomes - Sorensen, Amanda E.; Jordan, Rebecca C. (Frontiers in Environmental Science, 2025)
IntroductionThere has been little work investigating the effect of framing in citizen science and the subsequent effects on data quality and participant outcomes (e.g., science literacy, trust in science, motivations to contribute).MethodsTo establish the impact of framing in citizen science on data quality and participant outcomes, an experimental web-based citizen science program was created where participants were engaged in tree phenology research. Participants were randomized to one of two differently framed conditions where they were engaged in the same exact data collection task, but the rhetoric around participant contribution was framed differently. In this, participants were either referred to as a “Citizen Scientist” or “Volunteer.” Participants took a pre and post survey that measured science literacy, trust in science, and motivations to contribute to citizen science.ResultsThere were significant differences in participant outcomes and data quality between the two conditions post-participation. Individuals in the “Citizen Scientist” condition completed the project and submitted higher quality data significantly more than those individuals in the “Volunteer” condition. Additionally, individuals in the two conditions begin to diverge in their responses to questions within each of the measured areas post-participation.DiscussionThis research suggests that being called a citizen scientist may elicit internally held expectations of contribution, informed by normative and culturally informed experiences. Therefore, participants might view their contributions as citizen scientists are more consequential than when as volunteers. Research of this nature can help guide practitioners using citizen science in thinking about framing as a part of their project development and stimulate further research on best practices in citizen science project design.